Energetic rehabilitation in buildings: cost-effective solutions to minimise thermal bridging - Abreu, Maria Isabel (2010)
Nowadays, the energetic rehabilitation of buildings constitutes an increasing concern of national and international bodies, as a result of a strategic policy towards energy efficiency. In Portugal, one of the most current problems in buildings is thermal bridging. This is a significant source of heat building loss. The prevention of these types of pathologies is essential, for there are an enormous number of existing buildings that reveal such problems and therefore require rehabilitation. New building regulations on thermal behaviour and energy efficiency were recently enacted by the Portuguese Government, following the European Union Directive 2002/91/CE. To cope with the prescriptions of the new regulations, a better thermal quality in the building envelope is required. The rehabilitation of buildings is becoming a great issue. This study is part of wider research to investigate cost-effective constructive solutions of rehabilitation for the improvement of envelope thermal behaviour. From the results of previous studies which characterized the most current and problematic envelope zones, a simulation computer program was used to test the behaviour of several different solutions in order to minimise pathologies caused by thermal bridging. Preliminary results show that it is possible to get adequate solutions that fit harmoniously with the architecture of façades and with decoration of the internal spaces. Further studies will be needed to provide construction designers and builders with appropriate solutions to make the rehabilitation process even easier.